Electrochromic films of NiOx and WOxPy obtained by pyrolytic spraying - Gómez León, Mónica Marcela (1998)
Electrochromic nickel and nickel oxide thin films were obtained using the pyrolytic sputtering technique. The nickel oxide films were obtained in two ways. One using alcoholic solutions of Ni(NO3)26H2O, and the other using aqueous  solutions Ni(NO3)26H2O with the addition of small amounts of Co(NO3)26H2O.The deposition temperature for both cases was 300°C. Both show pronounced electrochromism; particularly in the second case when the Ni(NO3)2: Co(NO3)2 ratio is 90:10 a 50% change of transmittance is obtained in the visible range.Tungsten-phosphorus oxide films were obtained from a WOx sol to which phosphoric acid was added. The sol was prepared by ion exchange of Na2WO4.2H2O in a strongly acidic resin. The deposition temperature was 430°C. A significant increase in the loading capacity of WOx was observed as the proportion of P in the film increases.